(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
This research was conducted to identify the stakeholders involved in the management, analyse the interests, objectives, and potential conflicts that may arise among these stakeholders, and create scenarios based on the analysis conducted to improve the success of Tourism Village management. The MACTOR technique was used to analyse the roles and contributions of the stakeholders, and the MICMAC technique was used to identify factors that influence and are influenced by each stakeholder, which were obtained through interview data, observations, and literature studies. The combination of the MACTOR and MICMAC techniques, as well as the descriptive and quantitative approaches, resulted in the analysis of the main findings of the study, showing the complex dynamics among stakeholders in the management of the Tourism Village. Pokdarwis (Tourism Awareness Group) was found to play a major role in influencing other stakeholders, while the Maros-Pangkep Geosite showed a high dependency on the collaboration of other stakeholders to preserve the karst environment, and investors need to collaborate and coordinate across all stakeholders involved. These findings emphasise the importance of strong coordination and collaboration between stakeholders to ensure sustainable management of tourism villages and avoid conflicts of interest. In the scenarios developed, effective collaboration between the government, local communities, NGOs, tourism businesses, and investors proved to be the key to sustainable tourism village development. This research contributes to the understanding of policy makers, academics, and tourism practitioners on how to identify and analyse interests, alliances, and conflicts among stakeholders in tourism destination management in designing collaborative strategies.